Better procurement is essential to transform infrastructure delivery in this time of crisis. Issue 2 (May 2022) - Dyer, Thomas
Abstract : Thomas Dyer of Turner & Townsend says Brexit, Covid-19 and climate change have highlighted the need for serious improvement in UK infrastructure procurement practice. The government's new procurement bill and greater use of NEC4 contracts will be part of a much-needed transformation.